2005
DOI: 10.1007/s00253-004-1802-4
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the polyene macrolide antibiotic nystatin in Streptomyces noursei

Abstract: The polyene macrolide antibiotic nystatin, produced commercially by the bacterium Streptomyces noursei, is an important antifungal agent used in human therapy for treatment of certain types of mycoses. Early studies on nystatin biosynthesis in S. noursei provided important information regarding the precursors utilised in nystatin biosynthesis and factors affecting antibiotic yield. New insights into the enzymology of nystatin synthesis became available after the gene cluster governing nystatin biosynthesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…Notably, both the cytochrome P450 NysN and ferredoxin NysM believed to install nystatin's carboxylate at C16 (37) are absent in the selvamicin cluster, consistent with selvamicin's unoxidized methyl substituent at C12. The aminotransferase responsible for ammonium installation on the mycosamine sugar, NysDII, is also absent from the selvamicin cluster.…”
Section: Chemistrymentioning
confidence: 79%
See 1 more Smart Citation
“…Notably, both the cytochrome P450 NysN and ferredoxin NysM believed to install nystatin's carboxylate at C16 (37) are absent in the selvamicin cluster, consistent with selvamicin's unoxidized methyl substituent at C12. The aminotransferase responsible for ammonium installation on the mycosamine sugar, NysDII, is also absent from the selvamicin cluster.…”
Section: Chemistrymentioning
confidence: 79%
“…The bioinformatically identified selvamicin cluster resembles known type I PKS-derived polyene BGCs (30)(31)(32)(33)(34)(35), and a side-by-side comparison with the well-characterized nystatin BGC (36,37) readily reveals the origins of selvamicin's unusual structural features (Fig. 5).…”
Section: Chemistrymentioning
confidence: 99%
“…The broad range of biological activities exhibited by macrolides, including antibacterial (35), antifungal (36), and antiproliferative (37) activities, prompted us to investigate the biological activity of the stambomycins. They showed moderate activity against Gram-positive bacteria (SI Appendix, Table S6) but no activity against Gram-negative bac- teria, or fungi.…”
Section: J H-h Coupling Constants Of ∼15 Hz For H-12/h-1and H-48/h-49mentioning
confidence: 99%
“…Postpolyketide modifications of macrolides by cytochrome P450 (P450 or CYP) 2 hydroxylases provide molecular diversity to these macrolides during their biosynthesis (2,3). P450s are hemoproteins whose fifth axial heme iron ligand is a thiolate group found in a variety of organisms (4,5).…”
mentioning
confidence: 99%
“…Analysis of P450 gene deletion mutants revealed that CYP105P1 and CYP105D6 catalyze hydroxylations at posi-tions C26 and C1Ј, respectively. 3 The amino acid sequence identity between CYP105P1 and CYP105D6 is 36.7% when the whole lengths of both sequences are used for alignment.…”
mentioning
confidence: 99%